PENGARUH PENERAPAN MODEL PEMBELAJARAN MODIFIED INQUIRY BERBANTUKAN LEMBAR KERJA SISWA TERHADAP HASIL BELAJAR IPA SISWA DI KELAS VIII SMPN 2 PARIAMAN - Putri Bullquis Marsa; Asrul Asrul; Gusnedi Gusnedi (Universitas Negeri Padang, 2015)
One reason why low student achievement is method of lecturer which is dominant used by teacher in learning process, so it makes students aren’t active in learning. One solution of this problem can be solved by applied Modified Inquiry learning model assisted student worksheet. The purpose of this research is to investigate the effects of applied modified inquiry assisted student worksheet to student’s science learning outcomes in class VIII2 SMPN 2 Pariaman. This research is quasi experiment research with randomized control qroup only design. This population in this research were all of students of class VIII2 SMPN 2 Pariaman listed at 2014/2015 year academy. Sampling technique was purposive sampling. Samples of the research are class VIII2 as experiment class and class VIII3 as control class. Datas of this research are outcomes of cognitive, affective, and pschycomotor. Instruments of the research are written test at cognitive domain, observation sheet at affective domain, and performance sheet at pschycomotor. The data analysis technique used two average similar test at significant level 0,05. This research shows the average value of cognitive domain, affective domain, and pschycomotor domain of experiment class are 76,18, 78,25, and 80,51 which is higher then control class’s average value are 50,48, 72,92, and 76,20. Data analysis shows tcount at cognitive domain is 9,21, at affective domain is 2,76, and at pschycomotor is 2,55, to significant level 0,05 tcount of three of the domains are bigger than ttabel (ttabel=1,67). It can be concluted that there are effects of applied Modified Inquiry learning model assisted student worksheet to student’s science learning outcomes in class VIII2 SMPN 2 Pariaman